An interactive program for teaching Arabic Language for the non-native speakers - Ahmed Mahmoud, Ahmed Ragheb; Ahmad H.Osman, Rahmah; Sahrir, Muhammad Sabri (2012)
This research tries to lay the idea of an interactive program for teaching Arabic Language for the non-native speakers. This program will be established on the complete awareness of the language contents and its four study levels (phonological, morphological, syntactical and semantic) with a clear stress on the most prominent foundations and theories concerned with the academic accomplishment depending on the data system of the e-learning. The research has been established on textual and phonological database, comprehending the vocabulary of the language and its pronunciation ways and inferring the most important errors expected from the non-native speakers of Arabic. More than a hundred and twenty user have participated in the process, under the supervision of specialized teamwork—administrative, linguistic, educational and engineering. The tentative results has statistically reflected the program efficiency and its distinctive role in prompting the academic process and the increase of the cognitive outcome for the specimen of students who have been subject to this study as an experimental sample, compared to the results of the realizable control sample that took the same dose of a conventional education. This program has gained practical and academic features that make it more worth-studying than the other e-learning programs, because it does not only lay the theoretical foundations supported with modern methodological designs, but also it ensures the efficient and participatory role of the user in it.